A emergência do aluno-trabalhador no Brasil no contexto do PROEJA - Dullius, Rodrigo (Universidade do Vale do Rio dos Sinos, 2019)
This research, with archeogenealogical inspiration from Foucauldian Studies in Education, examines the emergence of the working student in policies for both professional education, and young and adult education in Brazil. The specific focus is on students participating in the National Program for Integration of Professional Education with Basic Education in the Young and Adult Education modality (PROEJA) in the present. The main methodological-theoretical operator that has intertwined the whole problematization here proposed is Foucault’s concept of discourse, understood as a practice that produces the objects of which it speaks. The research involved both a documental analysis examining Brazilian laws from the 16th to 21st century, totalizing 106 documents, and five focus groups with students attending a PROEJA Management course in a Federal Institute in the highlands of Rio Grande do Sul in 2017 and 2018. The analyses were subdivided into periods related to regularities and displacements, as follows: Education and the gentiles (1548-1798); The Empire and attempts at adult education (1808-1888); The Republic and the learners (1889-1931); Literacy and professionalization (1934-1985); The entrepreneurial self (1988-2018). Along these periods, we have moved from a sovereign society, with its punishment and exclusion practices aimed at getting the subjects out of an alleged state of savagery; to a disciplinary society, with its inclusion and correction practices; to a regulating society, in which the connection between education and work consists of a strong security dispositive derived from the governmentalization of the State, started in the 18th century; to the contemporary performance society. This does not mean that there have been replacements; rather, there have been couplings that keep certain regularities, such as: the working student’s place of (age, moral, intellectual) lack; the statement of aptitude; the statement of the risk of idleness and vagrancy (regarded as crimes at some moment); the policies of professional education, which are mostly intended for children and adolescents; the separation by gender and social class; the exclusion of the Indigenous and African-Brazilian populations from the public policies, in a country that has passed from an agrarian to an industrial society, and has been crossed by the perspective of the contemporary capitalism, which has operated with the statements of flexibilization, competences and multi-functionality. Hence, we mean an entrepreneurial self, associated to the precariousness of work relations, rather than entrepreneurship propagated as the solution to both the economic crisis and the employability problem.
Keywords: Aluno-trabalhador; PROEJA; Legislação educacional; Discurso; Arque genealogia; Working student; PROEJA; Education law; Discourse; Archeogenealogic; ACCNPQ::Ciências Humanas::Educação